2021
DOI: 10.4251/wjgo.v13.i12.2114
|View full text |Cite
|
Sign up to set email alerts
|

Propofol induces ferroptosis and inhibits malignant phenotypes of gastric cancer cells by regulating miR-125b-5p/STAT3 axis

Abstract: BACKGROUND Gastric cancer is a common malignancy with poor prognosis, in which ferroptosis plays a crucial function in its development. Propofol is a widely used anesthetic and has antitumor potential in gastric cancer. However, the effect of propofol on ferroptosis during gastric cancer progression remains unreported. AIM To explore the function of propofol in the regulation of ferroptosis and malignant phenotypes of gastric cancer cells. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
1
20
2
Order By: Relevance
“…In addition to the inhibition of apoptosis, the activation of STAT3 is associated with the inhibition of ferroptosis and pyroptosis. It was found that propofol increased the levels of ROS and free iron in gastric cancer cells, which led to ferroptosis, and overexpression of STAT3 inhibited propofol-induced ferroptosis [ 82 ]. Another study found that apatinib and cinobufagin encapsulated in a pH-responsive liposome induced pyroptosis and apoptosis in gastric cancer cells via the VEGFR2/STAT3 signaling pathway [ 82 ].…”
Section: Regulation Of Cell Death In Gastric Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the inhibition of apoptosis, the activation of STAT3 is associated with the inhibition of ferroptosis and pyroptosis. It was found that propofol increased the levels of ROS and free iron in gastric cancer cells, which led to ferroptosis, and overexpression of STAT3 inhibited propofol-induced ferroptosis [ 82 ]. Another study found that apatinib and cinobufagin encapsulated in a pH-responsive liposome induced pyroptosis and apoptosis in gastric cancer cells via the VEGFR2/STAT3 signaling pathway [ 82 ].…”
Section: Regulation Of Cell Death In Gastric Cancermentioning
confidence: 99%
“…It was found that propofol increased the levels of ROS and free iron in gastric cancer cells, which led to ferroptosis, and overexpression of STAT3 inhibited propofol-induced ferroptosis [ 82 ]. Another study found that apatinib and cinobufagin encapsulated in a pH-responsive liposome induced pyroptosis and apoptosis in gastric cancer cells via the VEGFR2/STAT3 signaling pathway [ 82 ]. This new drug encapsulated by pH-responsive liposomes has better solubility and targeting ability compared with unencapsulated apatinib and cinobufagin, which improves drug effects and reduces adverse drug reactions [ 82 ].…”
Section: Regulation Of Cell Death In Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Propofol can inhibit the proliferation and induce the apoptosis of GC cells. Propofol induced ferroptosis and inhibited malignant phenotypes of GC cells via the miR-125b-5p/STAT3 axis ( Liu Y. P. et al, 2021 ). The data of Gomaa et al identified a new mechanism mediating miR-4715-3p silencing and AURKA induction in upper gastrointestinal adenocarcinoma.…”
Section: Ferroptosis-related Non-coding Rna and Gastric Cancermentioning
confidence: 99%
“…Etomidate inhibits ischaemia/reperfusion (I/R)-induced ferroptosis through the Nrf2 pathway and alleviates myocardial injury, which may supply a fresh idea for clinical reperfusion therapy ( Lv et al, 2021 ). For cancerous cells, anaesthetics such as bupivacaine, propofol, and ketamine can induce ferroptosis and play an anticancer effect ( He et al, 2021 ; Hao et al, 2022 ; Liu et al, 2021a ). In an ALI model, both sevoflurane and DEX inhibited cellular ferroptosis and protected lung function ( Liu et al, 2021b ; Lin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%